From Sticks to Speech: Stick Puppet as an Alternative Media to Improve Seventh Graders’ Speaking Skill - Wahyuni, Luluk; Humairoh, Mega Fariziah Nur (Universitas Muhammadiyah Jember, 2023)
The focus of teaching English as a foreign language has primarily revolved around the importance of speaking skills. However, it has been observed that many students face challenges in improving their ability to speak. These challenges can be categorized into five main issues: linguistic aspects, psychological aspects, teaching strategies employed by teachers, inadequate media resources, and students' speaking performance. In light of these issues, the researcher proposed stick puppets as an alternative media that aligns well with the targeted aspects and strategies for improvement. This study employed Classroom Action Research (CAR) to enhance the speaking skills of seventh-grade students in SMPN 1 Bantaran during the academic year 2021/2022. Collaborative classroom action research was conducted, consisting of a single cycle spanning three meetings and one post-test. Data collection techniques included a speaking test to assess students' speaking scores, as well as teacher's field notes, interviews, students' questionnaires, and classroom observation sheets as secondary data. After implementing stick puppets as a media tool, the research findings revealed a significant improvement in the speaking skills of seventh-grade students. Out of 22 students, 95.65% achieved the minimum passing score, and the mean score increased from 16.08 in the preliminary speaking test to 90.86. The data indicated that the utilization of stick puppets contributed to enhancing students' vocabulary, pronunciation, grammar, and content in speaking. Additionally, stick puppets fostered increased participation and engagement among students in the classroom. Students displayed interest, motivation, and confidence, particularly when describing physical appearances using stick puppets.